The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/0100-29452017369
|View full text |Cite
|
Sign up to set email alerts
|

‘Fuji’ Apple Tree Response to Phosphorus Fertilization

Abstract: -The aim of this work was to evaluate the effects of orchard fertilization with increasing rates of phosphorus (P) on yield and critical levels of P in the soil and in the leaf of 'Fuji' apple trees. The experiment was conducted in São Joaquim, state of Santa Catarina, southern Brazil, from 2010 to 2015, in an Inceptisol soil. The three apple orchards were planted in 2004 with the Fuji cultivar grafted on Marubakaido/ M9 rootstock and grown under a high-plant-density system (1984 trees ha -1 ). Annual fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Differences in the ability of plants to acquire P exist among different species or varieties within a single species [8][9][10]. Genetic improvement of P efficiency in plants, as achieved through the breeding of P-efficient cultivars, has been utilized to optimize plant production under lower fertilizer use conditions [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the ability of plants to acquire P exist among different species or varieties within a single species [8][9][10]. Genetic improvement of P efficiency in plants, as achieved through the breeding of P-efficient cultivars, has been utilized to optimize plant production under lower fertilizer use conditions [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, its uptake rates are low. The studies by Nava et al (2017) and Stiles (1994) showed no response to P for apple. Neilsen et al (2008) noted that apple has very low demand for P and that historically studies showed no response to added P. However, they showed increased P uptake and 20% yield increase with P fertigation across several cultivars in their own work.…”
Section: Root Morphology and Architecture Of Key Speciesmentioning
confidence: 95%
“…In Poland, WOJCIK & WOJCIK (2007) applied phosphate and phosphate plus lime to a P deficient 'Jonagold' orchard and reported no increases on fruit yield due to soil P application when the soil pH was adequate. In Brazil, the only paper in the literature reporting the effect of P addition to the soil on apple orchards showed no increases on fruit yield (NAVA et al, 2017).…”
Section: Soil Sciencementioning
confidence: 95%
“…In our study, fruit from all treatments, including the control, always had P concentrations above 100mg kg -1 , which is adequate for long-term storage. This high P uptake in the control can possibly be explained by the amount of P released from the organic matter decomposition (NAVA et al, 2017) and by the contribution of mycorrhizae (GASTOL et al, 2016).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation